CNES technical considerations on space traffic management. (February 2020) - Bonnal, Christophe; Francillout, Laurent; Moury, Monique; Aniakou, Ursula; Dolado Perez, Juan-Carlos; Mariez, Julien; Michel, Sylvain
Abstract: The past 12 years, following the Feng-Yun 1C fragmentation in 2007, have witnessed a continuous increase of the orbital population, with more than 8000 new objects, representing 40% of the current orbital population. These additional objects are mostly debris, as there were only than 25% additional operational satellites compared to 12 years before. The coming 10 years may have their lot of surprises as well, with the emergence of new kind of assets in orbit including streams of very small non-maneuverable satellites, and constellations of medium size spacecraft devoted to internet. In parallel, new services are being developed, such as On-Orbit-Servicing, space tugs, potentially space debris remediation missions... As a consequence of such past and predictable evolution, it appears logical that numerous actors identify some need for a space traffic management, in order to achieve some sustainability of our orbital operations. CNES, and generally speaking France, have been proactive in this domain since decades. France was the first country to adopt a law dealing with the orbital operations in the constrained orbital environment, including space debris mitigation, and dedicated teams work on the topic for both spacecraft and launcher activities. France also benefits from a radar and telescope network enabling a national catalog to be maintained. CNES has developed all the tools necessary for the proper understanding of the current and future situation, enabling us to play a major role in all the international fora on the subject. CNES has also developed in line with NASA CARA the first "middle-man" service dealing with the conjunction data messages, leading to a very efficient collision avoidance service. This experience could well turn out to be fundamental in the preparation of potential actions in near future, discussing the need for, and helping define, an international coordination of the space traffic.